The proliferation and migration of atherosclerosis‐related HVSMCs were inhibited by downregulation of lncRNA XIST via regulation of the miR‐761/BMP9 axis. Issue 1 (1st October 2021) - Mo, Long; Jiang, Heng‐Bo; Tian, Gui‐Ru; Lu, Gui‐Jing
Abstract: Atherosclerosis (AS) is a chronic inflammatory disease that can be caused by the proliferation and migration of human vascular smooth muscle cells (HVSMCs). Here, we found that lncRNA XIST was related to the abnormal proliferation and migration of HVSMCs, and thus, the mechanism by which XIST regulated HVSMCs was further investigated. HVSMCs were treated with oxidized low‐density lipoprotein (ox‐LDL, 100 μg/ml) as AS models. CCK8 assays, flow cytometry, Transwell assays and wound healing assays were applied to evaluate cell viability, cell cycle analysis, and cell migration, respectively. A dual‐luciferase reporter assay was employed to verify the binding relationships between XIST and miR‐761, miR‐761, and BMP9. Ox‐LDL induced the proliferation and migration of HVSMCs, upregulated the expression of XIST, downregulated miR‐761 expression, and activated the BMP9/ALK1/endoglin pathway. Luciferase assays revealed that XIST sponged miR‐761. XIST knockdown ameliorated ox‐LDL‐mediated effects in HVSMCs, which were largely abolished by miR‐761 silencing. BMP9 was targeted‐inhibited by miR‐761. MiR‐761 overexpression alleviated ox‐LDL‐mediated effects in HVSMCs. However, BMP9 overexpression abolished miR‐761‐mediated effects in HVSMCs treated with ox‐LDL. Our findings suggested that XIST knockdown suppressed the proliferation and migration of HVSMCs by promoting miR‐761, which targeted‐inhibited the BMP9/ALK1/endoglin pathway.